Implementasi Pelaksanaan Pelatihan Kelompok Sadar Wisata Untuk Meningkatkan Pengetahuan Sapta Pesona Di Objek Wisata Gua Pancur Desa Jimbaran Kabupaten Pati - Aprilian Putra Pratama; Sunyoto Sunyoto; Made Prasta Yostitia Pradipta (Sekolah Tinggi Pariwisata Sahid Surakarta, 2019)
The purpose of this study was to determine the training given to Pokdarwis about sapta charm and to what extent the application of sapta charm in Goa Pancur Tourism Object, using quantitative descriptive research methods with data collection techniques through observation, interviews and documentation. The result of this research is that Pokdarwis, which initially did not know the Sapta Pesona material, became tofu and easy to apply in Goa Pancur Tourism Object. In addition, the Goa Pancur TourismObject which was previously still empty of visitors, now the Pancur Cave Tourism Object is very crowded with visitors and has become a Leading Tourist Object in Pati Regency